Investigaciones interdisciplinares en los saladeros orientales de Baelo Claudia - Darío Bernal-Casasola; José Á. Expósito Álvarez; José J. Díaz Rodríguez; Ricard Marlasca Martín (Mélanges de la Casa de Velázquez, 2017)
This article presents the results of the archaeological fieldwork carried out in 2015 in the eastern sector of the industrial quarter of Baelo Claudia, which has uncovered important evidence of on-site fish-salting and sauce-making activity, using as raw materials tunids and clupeidiae respectively. These exceptional finds have not only produced information of great interest from an ichthyologic standpoint, but they also tend to confirm that these new fish-salting works currently under investigation (Industrial Units XI and XII) are the largest of any so far discovered at Baelo Claudia, thus helping to gain a clearer idea of the real scale of the fish-based industries in this particular town, and by extension in the Fretum Gaditanum.